Budgeting Participation, Managerial Roles and Competence on Financial Management Performance - Andri Irawan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study investigates the effect of budgeting participation, managerial roles, and competencies on financial management performance at the Jayapura Main Port Authority Office. The data in this study used primary data collected by distributing questionnaires to all respondents filled in with several statements with five answer options that would be weighted scores. The collected data will be analyzed through four stages of testing. The first stage is to conduct a descriptive analysis. The second stage is to conduct a data quality test consisting of a validity and reliability test. The third stage is the classical assumption test (normality test, multicollinearity test, heteroscedasticity test). The fourth stage is to test all hypotheses proposed in this study, which will be proven through partial tests and the coefficient of determination test. The research findings reveal that despite high levels of budgeting participation and favorable perceptions of managerial roles and employee competencies, only competencies significantly improve financial management performance. Despite positive views of budgeting participation and managerial roles, neither showed a statistically significant influence on performance outcomes. This study underscores the importance of subordinate involvement in budgeting and the need for professionalism, transparency, and accountability in government financial management. The study confirmed the statistical validity of the model, including normality, absence of multicollinearity, homoscedasticity, and autocorrelation. The implications of these findings suggest that future research should consider alternative decision-making processes and strategies to enhance competencies, thereby improving financial management performance in similar government environments.